Case–control exercise challenge study on the pathogenesis of high serum gamma‐glutamyl transferase activity in racehorses. (25th May 2022) - Mann, Sabine; Abuelo, Angel; Stokol, Tracy; Wakshlag, Joseph J.; Bayly, Warwick; Reed, Steven; Gandy, Jeff; Ramsay, Joshua David; Divers, Thomas J.
Abstract: Background: High serum γ‐glutamyl‐transferase (GGT) activity syndrome in racehorses has been associated with maladaption to exercise. Investigation of affected horses before and immediately after standard exercise may provide critical insight into the syndrome's pathophysiology. Objectives: To investigate blood biomarker changes in actively competing racehorses with high GGT activity associated with an exercise challenge. Study design: Case–control study. Methods: High GGT case (age: 2–3 years) and normal GGT control (age: 2–7 years) pairs (3 Thoroughbred, 4 Standardbred pairs) at least 3 months into their training/racing season were included. Horses with a recent history of high GGT activity (≥50 IU/L) without additional biochemical evidence of liver disease were identified by veterinarians. Horses were tested again in the week prior to a planned exercise challenge to confirm persistent increases in GGT activity. Controls from the same stable with similar training/racing intensity and serum GGT activity ≤36 IU/L were matched with each case. Blood samples were obtained immediately before, 15 and 120 min after exercise. Pre‐exercise serum samples were analysed for baseline select serum chemistries, selenium and vitamin E concentrations. Cortisol concentration and markers of oxidative status were measured in serum or plasma for all time points. Individual serum bile acid and coenzyme Q10 concentrations, plasma lipid mediator (fatty acids, oxylipids, isoprostanes) concentrations and targeted metabolomics analyses were performed using liquid chromatography‐mass spectrometry. Serum viral PCR for equine hepaci‐ and parvovirus was performed in each animal. Results: Cases had higher baseline concentrations of total glutathione, taurocholic acid, cortisol and cholesterol concentrations and higher or lower concentrations of specific oxylipid and isoprostane mediators, but there were no case‐dependent changes after exercise. Main limitations: Small sample size. Conclusions: Results indicated that glutathione metabolism was altered in high GGT horses. Enhanced glutathione recycling and mild cholestasis are possible explanations for the observed differences.